HUBUNGAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR GAMBAR TEKNIK SISWA KELAS X JURUSAN TEKNIK GAMBAR BANGUNAN SMK NEGERI 2 SAWAHLUNTO - Muhammad Bayu; Juniman Silalahi; An Arizal (Universitas Negeri Padang, 2018)
Abstract This research is based on the lack of learning motivation for students on the eyes lesson Draw Technique class X students majoring in Building Image Engineering SMK Negeri 2 Sawahlunto. This study aims to determine whether or not there is a relationship of learning motivation with the results of learning subjects Image Engineering students Class X Department of Building Materials Engineering SMK Negeri 2 Sawahlunto. The type of this research is descriptive correlational research Population in this research is all student of class X Department of Building Image Engineering SMK Negeri 2 Sawahlunto academic year 2016/2017 amounted to 27 people, because the population is less than 100 then the sample taken all members of the population called Total Sampling amounted to 27 students. The variables in this study are the learning motivation as the independent variable (X) and the learning result of the Technical Drawing as the dependent variable (Y). Based on the results of this study can be concluded that there is a strong and significant relationship between learning motivation and learning outcomes. This can be seen from the correlation coefficient rxy (0.756)> rtabel (0.381). Keywords: Motivation, Learning, Learning Outcomes